1982
DOI: 10.1038/bjc.1982.113
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of preoperative serum CEA level compared to clinical staging: Ii. Stomach cancer

Abstract: Summary.-In a clinical investigation of postoperative survival after primary surgery for stomach cancer, 390 patients were registered since 1974. The potential prognostic parameters examined within the first days of hospitalization for primary resection included age of the patients, operability, tumour extension (TNM classification) and tumour stages I-IV (UICC). Statistical treatment of the data revealed that each of the clinical parameters covers critical ranges associated with highly significant differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1
7

Year Published

1983
1983
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 11 publications
0
14
1
7
Order By: Relevance
“…This demonstrated that stage is clearly a prognostic factor, and that an improvement in the accuracy of the prediction could be achieved by adding the anatomical site of the primary tumour 0 --I'll90 or (Table II), but once these factors were taken into account the histology and biochemical variates did not add further information. Following the report of (Staab et al, 1982) the assessment of prognosis was also performed excluding those patients who died within 4 weeks of their operation; both stage and site remained the most important prognostic factors. Figure 2 shows the way in which the model predicts survival differences of male patients aged 67 years with tumours of various stages, and how the survival probability is worse in patients who have a high ACT level, compared to those in which these levels are within normal limits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This demonstrated that stage is clearly a prognostic factor, and that an improvement in the accuracy of the prediction could be achieved by adding the anatomical site of the primary tumour 0 --I'll90 or (Table II), but once these factors were taken into account the histology and biochemical variates did not add further information. Following the report of (Staab et al, 1982) the assessment of prognosis was also performed excluding those patients who died within 4 weeks of their operation; both stage and site remained the most important prognostic factors. Figure 2 shows the way in which the model predicts survival differences of male patients aged 67 years with tumours of various stages, and how the survival probability is worse in patients who have a high ACT level, compared to those in which these levels are within normal limits.…”
Section: Resultsmentioning
confidence: 99%
“…There is now a large body of evidence that preoperative high blood levels of carcinoembryonic antigen (CEA) in colorectal cancer and in gastric cancer will be associated with a decreased survival, especially of patients with locally advanced or metastatic tumours (Staab et al, 1981(Staab et al, , 1982Wanebo et al, 1978). However, the prognostic significance of slightly raised levels of CEA is still debatable (Goslin et al, 1980;Blake et al, 1982;Steel et al, 1982).…”
mentioning
confidence: 99%
“…[29] Dijagnostička osetljivost CEA za kolorektalni karcinom iznosi 70%, a specifičnost 95%. Posle adekvatne terapije nivo u serumu se vraća u granicama normale, dok ponovni porast koncentracije ukazuje na progresiju bolesti ili prisustvo metastaza [30].…”
Section: Klasifikacija Tumorskih Markera Na Biohemijskoj Osnoviunclassified
“…Povišene koncentracije CEA nalaze se u serumu pacijenata sa karcinomima drugih organa: jetre, pluća, dojke, pankresa, želuca, bubrega, jajnika, prostate kao i u nekim benignim stanjima: ciroza, upalne bolesti creva, hronične plućne bolesti, pankreatitis, benigna hipertrofija prostate [30].…”
Section: Klasifikacija Tumorskih Markera Na Biohemijskoj Osnoviunclassified
“…GUILLERMO BANNURA C. 1 , MIGUEL A. CUMSILLE G. 2 , ALEJANDRO BARRERA E. 1 , JAIME CONTRERAS P. 1 , DANIEL SOTO C. 1 , CARLOS MELO L. 1 , CLAUDIO ZÚÑIGA T. 1 1 Servicio y Departamento de Cirugía Hospital Clínico San Borja Arriarán. 2 Escuela de Salud Pública. Facultad de Medicina Universidad de Chile, Santiago, Chile.…”
unclassified